2023
DOI: 10.3389/fphys.2023.1063556
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in cardiovascular disease: Towards exercise regulation of mitochondrial function

Abstract: The morbidity and mortality of cardiovascular diseases are exceedingly high worldwide. Pathological heart remodeling, which is developed as a result of mitochondrial dysfunction, could ultimately drive heart failure. More recent research target exercise modulation of mitochondrial dysfunction to improve heart failure. Therefore, finding practical treatment goals and exercise programs to improve cardiovascular disease is instrumental. Better treatment options are available with the recent development of exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…This was mainly due to the significant elevation in the inflammation in the cardiac tissue and the associated mild decrease in mitochondrial function. Many studies demonstrated the direct relationship between inflammation and mitochondrial dysfunction in developing cardiovascular abnormalities [ [50] , [51] , [52] ]. There exist many reports that link inflammation between a high-fat diet and diseases [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly due to the significant elevation in the inflammation in the cardiac tissue and the associated mild decrease in mitochondrial function. Many studies demonstrated the direct relationship between inflammation and mitochondrial dysfunction in developing cardiovascular abnormalities [ [50] , [51] , [52] ]. There exist many reports that link inflammation between a high-fat diet and diseases [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type 2 diabetes are likely to develop heart failure (HF). HF canbe induced by pathological heart remodeling due to mitochondrial dysfunction [19]. Vice versa, the improvement in mitochondrial dysfunction can improve HF.…”
Section: Introductionmentioning
confidence: 99%